Comparison between turbinoplasty and endoscopic turbinectomy: Efficacy and clinical parameters - Rodrigues, Marcos Marques; Dibbern, Ralph Silveira; de Oliveira, Luis Francisco; Marques, Melania Dirce Oliveira; Bella, Marcelo Fernando; de Paula, Fausto Antonio, Junior; Araújo, Fernando Cesar França (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Nasal Obstruction is a common symptom and affects 25% of the population. The inferior turbinate hypertrophy is the main cause of nasal obstruction. In the failure of clinical control, a surgical procedure to reduce the size of the inferior turbinate is indicated.Objective: Compare the improvement of life quality in late postoperative of Turbinectomy and turbinoplasty.Method: Study of a retrospective case series. 24 patients were submitted to a nasal surgery of turbinectomy or turbinoplasty in 2007. The patients were invited to an interview in august of 2008. The patients were evaluated in the following items: Postoperative NOSE scale, morbidity in postoperative, bleeding and quantity of crusts in postoperative.Results: 24 patients attended for the evaluation. The main variable analyzed was the difference between NOSE scales in late pre and post operative. There was no statistically significant by the test in the variables studied. Discussion: In the evaluation of the various types of surgical treatment of the inferior turbinate, literature shows similar results to our study, finding similar results between many surgical techniques in the improvement of the nasal obstruction and in mucociliary activity.Conclusion: There are no evidence in the literature and in our sample of the superiority of a technique of surgical treatment in the inferior turbinate under other treatments.
Keywords: airway obstruction; nasal obstruction; rhinitis